Understanding the Mechanism of Nitrobenzene Nitration with Nitronium Ion: A Molecular Electron Density Theory Study. Issue 45 (5th December 2019) - Cyrille, Nana Nouhou; Idrice, Adjieufack Abel; Maraf, Mbah Bake; Charles, Fon Abi; Ibrahim, Mbouombouo Ndassa; Ríos‐Gutierrez, Mar; Domingo, Luis Ramon
Abstract: The nitration reaction of nitrobenzene with nitronium ion yielding ortho ‐, meta ‐ and para ‐dinitrobenzenes has been studied within the Molecular Electron Density Theory, using DFT computational methods at the B3LYP/6‐311G(d, p) level. This electrophilic aromatic substitution (EAS) reaction takes place through a two‐step mechanism involving the formation of a tetrahedric cation intermediate. The electrophilic attack of nitronium ion on nitrobenzene is the rate‐determining step of this EAS reaction, and consequently, responsible for the composition of the reaction mixture. The subsequent proton abstraction from the cation intermediate is barrierless. From the computed activation Gibbs free energies, a relationship 11.0 ( ortho ) : 87.3 ( meta ) : 1.7 ( para ) of the dinitrobenzenes is estimated, in clear agreement with the experimental outcome. The similar nucleophilic activation of the ortho and meta carbons of nitrobenzene makes it possible to question the hypothesis for the orientation in EAS reactions involving nucleophilically deactivated benzenes based on the relative stability of the tetrahedric cation intermediates. Abstract : According to the computed activation Gibbs free energies, the analysis of the nucleophilic Parr functions at nitroethylene suggests a similar ortho/meta regioselectivity against the classical analysis of the director effects of the substituents based on analysis of the resonance Lewis structures of the cation intermediates. The present Molecular Electron Density Theory study suggests that unfavourable non‐covalent interactions present along the ortho approach mode are responsible for the observed meta regioselectivity.